Β-NiS modified CdS nanowires for photocatalytic H2 evolution with exceptionally high efficiency. Issue 6 (8th January 2018) - Guan, Shundong; Fu, Xiuli; Zhang, Yu; Peng, Zhijian
Abstract : Synthesis of an exceptionally highly efficient NiS–CdS hybrid photocatalyst for H2 evolution. Abstract : Co-catalysis is regarded as a promising strategy to improve the hydrogen evolution performance of semiconductor-based photocatalysts. But developing a simple and effective technique to achieve the optimal synergy between co-catalysts and host photocatalysts has been a great challenge. Herein, hybrid photocatalysts consisting of β-NiS modified CdS nanowires (NiS/CdS NWs) have been synthesized via a simple and green hydrothermal route using CdS NWs as the template from thiourea and nickel acetate in the presence of sodium hypophosphite. As a result, a metal Ni intermediate was formed via an electroless plating process assisted by H2 PO2 −, which facilitated the growth of highly conducting flake-like β-NiS nanostructures onto the surface of the CdS NWs. With the optimal loading amount of NiS, the obtained NiS/CdS NWs present a record-high photocatalytic activity for H2 evolution in lactic acid aqueous solutions under visible light irradiation. At 25 °C, the rate of H2 evolution was measured as 793.6 μmol h −1 (over a 5 mg photocatalyst sample), which is nearly 250-fold higher than that over pure CdS NWs, and the apparent quantum yield reached an exceptionally high value of 74.1% at 420 nm. The mechanism for the photocatalytic H2 evolution over the present NiS/CdS NWs was also proposed. This strategy would provide new insight into the design and development of high-performance heterostructured photocatalysts.